Dietary risk factors for childhood asthma in a semi-urban area of South India: A cross-sectional study - Muraleetharan, G; Anuradha, G (Indian Journal of Child Health, 2019)
Background: Although inhaled allergens are more likely to trigger asthma than food allergens, global trends of asthma prevalence emphasize the role of changing dietary habits in modulating the inflammatory mediators involved in the pathogenesis of asthma. Objective: The objective of the study was to identify the dietary risk factors associated with childhood asthma in a semi-urban region of South India. Materials and Methods: This was a cross-sectional study done at a medical college hospital in South India from October 2016 to January 2017. After obtaining the Ethical Committee approval, children aged 3–15 years attending the pediatric outpatient department were enrolled in the study. Parents were interviewed with a precoded Food Frequency Questionnaire. Details regarding common dietary practices followed at home, frequency of consumption of specific food groups and history of food allergy were obtained. Chi-square tests and logistic regression analysis were used to analyze the data. Results: Among 500 subjects, 293 (58.6%) children had physician-diagnosed asthma. Duration of breastfeeding was 1 year), restriction of fast food, and avoidance of food additives decrease the risk of asthma in children. Non-vegetarian diet with the inclusion of fish offers a protective effect against asthma. Early identification and appropriate management of coexisting food allergies in children with asthma are necessary.